Autobiographical Impulses and Female Identity in the Drawings of Napachie Pootoogook - Berlo, Janet Catherine (Inuit Art Foundation, 2007)
In this article Berlo examines several drawings by the Cape Dorset artists Napachie Pootoogook. These drawings, which depict the artist in her contemporary life, differ in content from the majority Inuit drawings and prints of traditional life that circulate in the art market. Berlo suggests that both scenes of both contemporary and traditional life are important for the cultural production of contemporary Inuit identity.